1997
DOI: 10.1111/j.1096-0031.1997.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher Level Phylogeny of Curculionidae (Coleoptera: Curculionoidea) based mainly on Larval Characters, with Special Reference to Broad‐Nosed Weevils

Abstract: A cladistic analysis of Curculionidae was performed using 49 characters (41 from larvae, three from pupae, and five from adults). Illustrations of characters of immatures are provided. The analysis involved 19 terminal units and a hypothetical ancestor determined by the outgroup comparison method used to root the tree. One most parsimonious cladogram was obtained based on the complete data set and the following phylogenetic hypothesis is proposed: Ithycerinae, Microcerinae, and Brachycrinae sensu stricto are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 36 publications
7
76
0
3
Order By: Relevance
“…The presence of four ventral malar setae in larvae of the genus Strophosoma confirms the observations of Marvaldi (1998a) that this character, as well as the shape of the antennal sensorium (Marvaldi 1997(Marvaldi , 2003, can be considered an additional apomorphic character for larvae of the subfamily Entiminae, while other Curculionidae, e.g. Cyclominae in the sense of Marvaldi (1998bMarvaldi ( , 2003, possess the plesiomorphic number of five vms.…”
Section: General Remarks About the Morphology Of Strophosoma Larvaesupporting
confidence: 68%
See 1 more Smart Citation
“…The presence of four ventral malar setae in larvae of the genus Strophosoma confirms the observations of Marvaldi (1998a) that this character, as well as the shape of the antennal sensorium (Marvaldi 1997(Marvaldi , 2003, can be considered an additional apomorphic character for larvae of the subfamily Entiminae, while other Curculionidae, e.g. Cyclominae in the sense of Marvaldi (1998bMarvaldi ( , 2003, possess the plesiomorphic number of five vms.…”
Section: General Remarks About the Morphology Of Strophosoma Larvaesupporting
confidence: 68%
“…Photos were made using an Olympus BX63 microscope and processed by Olympus cellSens Dimension software. Names and abbreviations of body parts follow the terminology proposed by Scherf (1964), setae according to Anderson (1947) and May (1994), and mouthparts and antennae by Marvaldi (1997Marvaldi ( , 1998a. All specimens are deposited in the collection of the Department of Zoology, Maria Curie-Skłodowska University, in Lublin.…”
Section: Methodsmentioning
confidence: 99%
“…Although Platypodinae was traditionally considered an independent family within Curculionoidea (Wood 1986(Wood , 1993Wood and Bright 1992), it is now considered within the family Curculionidae (Kuschel et al 2000;Oberprieler et al 2007;Alonso-Zarazaga and Lyal 2009;Bouchard et al 2011;Jordal et al 2011Jordal et al , 2014. Extensive analyses by Kuschel et al (2000) and Farrell et al (2001) suggested that platypodines should be better classed as a group of scolytines (Jordal and Cognato 2012); however, other researchers, namely Marvaldi (1997) and Marvaldi et al (2002Marvaldi et al ( , 2008, concluded they were more suitably described as being independent subfamilies within Curculionidae. Jordal et al (2011) carried out an extensive phylogenetic study on the most prominent wood-boring taxa, within which they suggested that Scolytinae and Platypodinae were sister lineages within Curculionidae and that early diversification made them as advanced weevils.…”
Section: Introductionmentioning
confidence: 94%
“…The ancient origin of this superfamily (McKenna et al, 2009) along with the huge number of constituent taxa (Oberprieler et al, 2007) has made the understanding of its evolutionary relationships and its phylogenetic reconstruction challenging (Legalov, 2006). Some attempts to solve this problem have involved the use of morphological characteristics of subgroups or certain organ systems (Calder, 1989;Lyal et al, 2006;Marvaldi, 1997) and the use of molecular markers (Bocak et al, 2014;Caterino et al, 2002;Hundsdoerfer et al, 2009;McKenna et al, 2009;Robertson et al, 2008;Wild and Maddison, 2008). Nevertheless, both approaches have complications regarding the different compositions of the clades at different levels (Hundsdoerfer et al, 2009).…”
Section: Introductionmentioning
confidence: 97%